AGRICULTURAL ACCOUNTANCY IN POLAND – SELECTED THEORETICAL AND PRACTICAL ISSUES - Monika Turek-Radwan; Bogusław Wacławik (Zeszyty Naukowe Wyższej Szkoły Finansów i Prawa w Bielsku-Białej, 2016)
The paper presents selected issues related to agricultural accounting in Poland. The selection includes: a brief outline of the development of farm accounting in Poland, numerical figures characterizing Polish agriculture, selected issues related to the regulations contained in IAS 411 ’Agriculture’ and overview of the issues related to the introduction of income tax in agriculture.